"Fact-based dreaming" as climate communication. (3rd April 2022) - Hawley, Erin; Mocatta, Gabi
ABSTRACT: Documentaries have become an important avenue for climate change communication due to their ability to galvanize social change. Environmental documentaries have traditionally sought to motivate audiences through fear appeals, shock tactics, and a mode of address that is enraged, gloomy, chiding or disappointed. More recently, communication strategies for environmental documentary-makers have diversified, with positivity, playfulness, and solution-focused storytelling emerging as new possibilities for filmmakers seeking to inspire environmental change. The Australian documentary 2040 represents one such effort to "tell a new story" about climate change. In this article we explore 2040 's unique communication strategy of "fact-based dreaming": a process which involves mobilizing the creative power of imagination to subvert established thought patterns while anchoring such imagination in present-time reality. We assess this strategy and argue that fact-based dreaming, itself a "childlike" strategy, is most productive when it incorporates the voices, imaginings and perspectives of children and young people.